Sharing the burden of sickness : a history of healing and medicine in Accra - Roberts, Jonathan (Historian) (Indiana University Press, 2021)
"In Sharing the Burden of Sickness, Jonathan Roberts examines the history of the healing cultures in Accra, Ghana. When people are sick in Accra, they can pursue a variety of therapeutic options. West African traditional healers, spiritual healers from the Islamic and Christian traditions, Western clinical medicine, and an open marketplace of over-the-counter medicine provide ample means to promote healing and preventing sickness. Each of these healing cultures had a historical point of arrival in the city of Accra, and Roberts tells the story of how they intertwined and how patients and healers worked together in their struggle against disease. By focusing on the medical history of one place, Roberts details how urban development, colonization, decolonization, and independence brought new populations to the city, where they shared their ideas about sickness and health. Sharing the Burden of Sickness explores medical history during important periods in Accra's history. Roberts not only introduces readers to a wide range of ideas about health but also charts a course for a thoroughly pluralistic culture of healing in the future, especially with the spread of new epidemics of HIV/AIDS and ebola"--